Study of Power Density Transmitted from Cellular Base Station Towers of Nepal Telecom in Biratnagar Sub-Metropolitan City - Thapa, Dinesh; Sahu, Ram Bharosh; Parajuli, Prakash; Shah, Buddha Ram (International Journal of Applied Sciences and Biotechnology, 2016)
Background: In this present world, human beings are being exposed directly or indirectly to some kind of ionizing and non-ionizing radiations with the development of recent scientific technologies or by natural phenomena. The study of the measurement of power density (PD) or Radio Frequency (RF) radiated from cellular Base Station Towers (BSTs) is seemed to be important in Nepal like other countries because of its various health effects. In this study, the authors measured the PD radiated from mobile base station towers in Biratnagar sub-metropolitan city, Morang. Methods and Methodology: All together 18 BSTs were selected within Biratnagar for the study purpose. Tenmars TM-196 which is a non-ionizing radiation detector was used to measure the power density. The Global Positioning System (GPS), a space-based satellite navigation system was used to locate the Maximum Peak Point (MPP) from the BSTs. Result: The maximum power density (PD) was observed near Jogbani boarder i.e. 3781.0 µW/m2 which was 0.63% of the NTA guidelines. Similarly, the minimum power density was observed near Rani BRT i.e 1549.3 µW/m2which was 0.26% of the NTA guidelines. Conclusion: From the survey it can be concluded that there is no significant health hazard to the general people due to non-ionizing radiation radiated from Base Station Towers in Biratnagar. Int J Appl Sci Biotechnol, Vol 4(3): 338-345